1997
DOI: 10.1002/(sici)1099-1077(199706)12:2+<s79::aid-hup905>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Addiction, Personality and Motivation

Abstract: It is suggested that addictive behaviour, so called, ®ts into a psychological resource model. In other words, the habits in question are acquired because they serve a useful function for the individual, and the nature of the functions they ful®l is related to the personality pro®le of the`addict'. For some people this resource function develops into a form of addiction, and it is suggested that the reason this occurs is related to excessive dopamine functioning. This in turn is used to suggest the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 47 publications
3
48
0
4
Order By: Relevance
“…In partial support of our hypothesis, we found that higher levels of P and N, but not E, predicted greater alcohol consumption, which in turn predicted violent offending. These results are consistent with previous reports that offenders with high P levels show impulsivity, aggressiveness, and coldness in interpersonal relations [29], which can lead to both alcohol consumption and violent offences. Our results are also consistent with studies showing that alcohol consumption can be a coping strategy to escape negative internal experiences such as anxiety [30][31][32][33], which is associated with neuroticism.…”
Section: Discussionsupporting
confidence: 93%
“…In partial support of our hypothesis, we found that higher levels of P and N, but not E, predicted greater alcohol consumption, which in turn predicted violent offending. These results are consistent with previous reports that offenders with high P levels show impulsivity, aggressiveness, and coldness in interpersonal relations [29], which can lead to both alcohol consumption and violent offences. Our results are also consistent with studies showing that alcohol consumption can be a coping strategy to escape negative internal experiences such as anxiety [30][31][32][33], which is associated with neuroticism.…”
Section: Discussionsupporting
confidence: 93%
“…Within the Big Three approach to personality (L. A. Clark & Watson, 1999), psychoticism and neuroticism tend to be viewed as most relevant to addictions (e.g., Eysenck, 1997), although it is notable that drug addicts tend to have relatively lower scores on extraversion (see Eysenck, 1997, for a review). L. A.…”
Section: Healthy Behaviormentioning
confidence: 99%
“…On a theoretical level, researchers have had a continued interest in the role of personality in addictive behaviors (Eysenck, 1997). Per the DSM, there are three primary personality disorder clusters: Cluster A defined as odd or eccentric (i.e., Schizoid, Schizotypal and Paranoid); Cluster B characterized by erratic, dramatic, or labile emotions and behavior (Narcissistic, Borderline, Histrionic and Antisocial Disorders) and Cluster C personality disorder types described as having dependent and avoidant responses (i.e., Avoidant, Dependent, and Obsessive-Compulsive Personality).…”
Section: Pathological Gambling and Personality Disordersmentioning
confidence: 99%